What Can Intuition and Discourse Afford? - Rynkiewicz, Kazimierz (Hybris, 2012)
With a view of Husserl and Foucault the article ist seeking a critical epistemological phenomenological analysis of the relationship between the notions of intuition and discourse. The central question is: what can intuition and discourse afford? The epistemological performance of these terms is determined both generally and specifically. While the general performance highlights the establishment of the human subjects in the real world, it is the special performance with the access of subjects to the ideal objects. This situation requires the complementary pursuit, i.e., a synthesis of the intuition and the mind.